The effect of Applied Sakon Nakhon Traditional Thai Boxing Dance on physical Performance and Cardio-pulmonary Capacity in Thai Elderly Females - Piwngern, Teera; Suttitum, Tunda; Khrisanapant, Wilaiwan; Pasurivong, Orapin; Chumvangvapee, Pruchya (Srinagarind Medical Journal, 2016)
Background and Objective: Thai females in the elderly ages need to develop physical performance for maintaining their good health and good quality of life because they are in a high risk group of various chronic diseases. The objective of this study is to investigate the effects of 12-week applied exercise model of SNTB on physical performance and cardio-pulmonary function in Thai elderly females. Methods: Thirty Thai elderly females aged 61-70 years, body mass index (BMI) 23.0-29.9 kg/m2 with good health, no infectious diseases or severe chronic diseases are recruited as volunteer subjects. They are divided into two groups; control group (n=15) and applied SNTB exercise group (n=15). Both groups were assessed base-line clinical characteristics and physical performance such as hand grips, back and leg strengths and trunk flexibility tests including cardio-pulmonary capacity by measurement 6-minute walk test.Control subjects behave as their normal life styles in both exercise and eating behaviors all for a long 12 weeks of the study,while exercise groups are trained with applied SNTB exercise for 30 min/session (5 min warm up, 20 min exercise of 60-70% HR-max and 5 min cool down) at least 3 days/week in 12 consecutive weeks and eat as their normal life styles. Results: After 12 weeks of applied SNTB exercise, it was found that in exercise group versus control group there was an increase in high significance in hand grip test 30.85% and back strength test 68.87% (p<0.01), while there was an increase in high significance in leg strength test 69.58% and six-minute walk test (6 MWT) 39.93% (p<0.001). Conclusions: Twelve weeks of applied SNTB could increase physical performance and cardio-pulmonary capacity in Thai elderly females.Therefore, this applied SNTB exercise can be used as new exercise training for health promotion in Thai elderly females.